PEMODELAN INDEKS HARGA SAHAM GABUNGAN DAN VOLUME PERDAGANGAN DI BURSA EFEK JAKARTA MENGGUNAKAN ANALISIS RUNTUN WAKTU - -, Noeryanti (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
In order to give more complete information about stock exchange development to public, "Bursa Efek Jakarta" (BEJ) has spread out stockt value movement data through press and elec-tronic. From fifteen index data component available, the important indi-cator in stock value exchange is Daily Stock Value Index (IHSG) and Trade Volume. Base on data taken by researcher through website of Jakarta Stock Exchange (JSX) on data menu trade at http://www.jsx.co.id, it was obtained data exchange pattern of IHSG and Trade Volume for 358 days and the researcher extrapolated the datum to the next time (predict the next 90 datum) The result of analysis by using software Minitab v13 showed that the mode of quadratic trend pattern is very suitable for both datum. Trend equation of IHSG data is: Yt = 1085,53-0,581334t+4,21E-03t2 and trade volume is: Yt =0,972451-1,50E-04t+3,93E-07t2. Forecasts value for next 90 datum is useful for business user in long term. The pattern of both datum is stationary in the first difference. So Box-Jenkins mode can be formed for IHSG data is ARIMA(1,0,0), with the first mode:Zt = 0,0838 Zt-1 + at; at~indN(0,0.9296); ARIMA(1,0,1) with the first mode: Zt = -0,10498-0,2482Zt-1+at-0,3399at-1; at~ind N(0,0.84843) and ARIMA(1,0,0) with the first mode: Zt = -0,4273Zt-1+at;at~ind N(0,0.6046). With the same way it is obtained Box-jenkins mode for Trade Volume data : ARIMA(1,0,0) with the first mode: Zt= -0,4051Zt-1+at; at~ind N(0,32.0315), ARIMA(0,0,1) with the first mode:Zt = -4,73+at+0,7342at-1; at~ind N(0,6.0753) dan ARIMA(1,0,1) with the first mode: Zt = 3,9811-0,1706Zt-1+at+0,8230at-1Â; at~ind N(0,23.04)